A multiple objective approach to scheduling the preventive maintenance of modular aircraft components. (1st January 2011) - Joo, Seong-Jong; Min, Hokey
Preventive maintenance (or overhaul) is crucial for military aircraft operations because it dictates the mission readiness level and aircraft operating costs. For example, preventive maintenance not only improves the lifetime aircraft reliability/safety by avoiding unexpected equipment failure and downtime, but it also enhances the efficiency of managing spare-part by planning the replacements and replenishment of spare parts within the predetermined time interval. Despite such benefits, preventive maintenance may not be economical, unless its schedule is determined in such a way that its overall preventive maintenance costs including costs associated with the purchase of spare modules is less than the total costs of corrective actions including downtime/idle costs, repair costs, and mission failures. With that in mind, we propose a dynamic goal programming (GP) model that aims at determining the optimal number of spare modules, while meeting the scheduled due dates for preventive maintenance under budget constraints.